Beware biofilm! Dry biofilms containing bacterial pathogens on multiple healthcare surfaces; a multi-centre study. Issue 3 (November 2018) - Ledwoch, K.; Dancer, S.J.; Otter, J.A.; Kerr, K.; Roposte, D.; Rushton, L.; Weiser, R.; Mahenthiralingam, E.; Muir, D.D.; Maillard, J.-Y.
Summary: Background: Wet biofilms associated with medical devices have been widely studied and their link with healthcare-associated infections (HCAIs) is well recognized. Little attention has been paid to the presence of dry biofilms on environmental surfaces in healthcare settings. Aim: To investigate the occurrence, prevalence, and diversity of dry biofilms on hospital surfaces. Methods: Sixty-one terminally cleaned items were received from three different UK hospitals. The presence of dry biofilm was investigated using culture-based methods and scanning electron microscopy (SEM). Bacterial diversity within biofilms was investigated using ribosomal RNA intergenic spacer analysis (RISA)–polymerase chain reaction and next-generation sequencing. Findings: Multi-species dry biofilms were recovered from 95% of 61 samples. Abundance and complexity of dry biofilms were confirmed by SEM. All biofilms harboured Gram-positive bacteria including pathogens associated with HCAI; 58% of samples grew meticillin-resistant Staphylococcus aureus . Dry biofilms had similar physical composition regardless of the type of items sampled or the ward from which the samples originated. There were differences observed in the dominance of particular species: dry biofilms from two hospitals contained mostly staphylococcal DNA, whereas more Bacillus spp. DNA was found on surfaces from the third hospital. Conclusion: The presence of dry biofilms harbouring bacterial pathogens is virtually universal on commonly used items in healthcare settings. The role of dry biofilms in spreading HCAIs may be underestimated. The risk may be further exacerbated by inefficient cleaning and disinfection practices for hospital surfaces.